Removal of polycyclic aromatic hydrocarbons by biosorbents - José, Sílvia S. (2020)
Introduction: - Polycyclic aromatic hydrocarbons (PAHs) are a group of environmental carcinogens. They are formed during the incomplete combustion of organic matter. Humans are exposed to PAHs by various sources, including occupational environments, cigarette smoke, vehicle exhaust, and dietary sources as grilled and flame-broiled food. - In vivo studies in animals proved that PAHs are associated to cancer, and epidemiologic studies with exposed workers, especially in coke ovens and aluminium smelters, have shown clear excess of lung cancer and highly suggestive excesses of bladder cancer. - These compounds can enter in drinking water sources by precipitation and runoff on the earth’s surface. - Portuguese legislation for water for human consumption (DL 306/2007) proposes the determination of five PAHs; limits of the maximum concentration are 0.10 µg/L for total BghiP, BbF, BkF, IcdP, and 0.010 µg/L for BaP.